THE IMPACT OF YOGA PRACTICE ON SPINAL HEALTH AND PSYCHOLOGICAL WELL-BEING IN THE ERA OF SEDENTARY DIGITAL LIFESTYLE - Chodań, Tamara; Ślusarczyk, Joanna; Pietrzyk, Piotr; Stanek, Natalia; Krawczyk, Patrycja; Łapaj, Maja; Jagiełło, Aleksandra; Noweta, Zuzanna; Lewicka, Milena`; Szreder, Beata (International Journal of Innovative Technologies in Social Science, 2026)
The contemporary landscape of human productivity has undergone a radical transformation, shifting from physical labor to a predominantly sedentary digital existence. This transition has institutionalized sedentary behavior (SB), defined by an energy expenditure of   metabolic equivalents (METs), as the primary occupational and leisure modality.1 This systematic research report investigates the multi-scalar impact of yoga practice on spinal integrity and psychological equilibrium within this hyperconnected, sedentary context. Epidemiological data indicates that over 80% of modern occupations are sedentary, with adults accumulating approximately 8.2 hours of sitting time daily.1 This lifestyle is directly associated with the proliferation of Upper Crossed Syndrome (UCS), "Text Neck," and chronic non-specific low back pain, resulting from predictable muscle imbalances and increased intradiscal pressure.3 Concurrently, the digital era has birthed "Burnout 2.0," a state of neuroendocrine exhaustion driven by temporal fragmentation and algorithmic intensification, which disrupts the Hypothalamic-Pituitary-Adrenal (HPA) axis and depletes Gamma-Aminobutyric Acid (GABA) levels.5This report synthesizes evidence from recent randomized controlled trials and meta-analyses to evaluate yoga as a "bio-psychosocial" intervention. Findings suggest that consistent yoga practice—ideally 2–3 sessions per week—can reduce morning cortisol levels by 27% and improve heart rate variability (HRV) by 42% through vagal nerve stimulation.7 Biomechanically, yoga demonstrates significant efficacy in correcting forward head posture (FHP) and improving cervical and lumbar range of motion (ROM) through core stabilization and proprioceptive refinement.9 The materials and methods section outlines a rigorous systematic framework for future clinical inquiry, emphasizing standardized reporting via the CLARIFY guidelines and objective assessment through digital goniometry and surface electromyography.11 Ultimately, this analysis underscores that yoga provides a synergistic mechanism for restoring human sustainability in an era of technological acceleration.